2014
DOI: 10.1007/s10681-014-1242-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving adaptation to drought stress in small red common bean: phenotypic differences and predicted genotypic effects on grain yield, yield components and harvest index

Abstract: Common bean (Phaseolus vulagaris L.) is mainly produced in Latin America, and Eastern and Southern Africa where seasonal rainfall is erratic and soil moisture deficit often limits its production. The objectives of this study were to identify superior advanced small red common bean lines with better grain yield under drought, and to identify plant traits that could serve as selection criteria for evaluating drought resistance. Thirty four advanced inbred lines were developed through triple cross and evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
6
44
1
Order By: Relevance
“…Drought stress is known to reduce yield components such as PNA and SNA (Rao et al, 2013; Assefa et al, 2015). Seed number per pod has been identified as useful criteria for selection for improving drought resistance because of its higher heritability and contribution to genetic gain (Ramirez-Vallejo and Kelly, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress is known to reduce yield components such as PNA and SNA (Rao et al, 2013; Assefa et al, 2015). Seed number per pod has been identified as useful criteria for selection for improving drought resistance because of its higher heritability and contribution to genetic gain (Ramirez-Vallejo and Kelly, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that drought‐tolerant lines in this study had relatively bigger seed sizes (SW values greater than 18 g) compared to the standard check (Awash‐1). This might be due to better seed filling that improved seed size and also improved seed quality (Assefa et al., ; Beebe et al., ). Besides contributing to GY, greater SW values could also be an advantage since bigger‐sized seeds have better canning quality and cooking time than the small‐sized seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient remobilization of photosynthate or greater partitioning of dry matter to grain yield has been emphasized as an important drought tolerance mechanism in common bean (Assefa et al., ; Beebe et al., ; Klaedtke et al., ). Recently, Polania et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations